2012
DOI: 10.1080/13607863.2012.657156
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived burdensomeness erode meaning in life among older adults?

Abstract: Background Identification of risk factors for loss of meaning in life among older adults is needed. In the current paper, we test hypotheses derived from the Interpersonal Theory of Suicide concerning the role of perceptions that one is a burden on others as a risk factor for lower meaning in life. Methods A prospective design was used to examine the temporal associations between perceptions of burdensomeness on others and perceived meaning in life among older adults (n = 65) seeking mental health treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Irrespectively, given the acceptance of PAS/EUT for cases of severe long-term care dependency in old age among more than one-third of the older population in Austria, it seems that discussions about PAS/EUT should not be restricted to terminally ill patients or to those suffering from physical pain per se. More generally, our results call for more attention within the debate on ELDs towards the situation of older adults who are tired of living22 due to a perceived loss of autonomy and dignity, due to loneliness or perceived burdensomeness in the context of prolonged care dependency, all of which can erode the meaning of life 23 24. In this respect, it is important to note that our study referred to attitudes among the general older population—rather than to preferences or the inclination to use PAS/EUT among actual care-dependent older adults—and, therefore, likely partially reflects negative stereotypes and fears about living as a care-dependent older adult.…”
Section: Discussionmentioning
confidence: 76%
“…Irrespectively, given the acceptance of PAS/EUT for cases of severe long-term care dependency in old age among more than one-third of the older population in Austria, it seems that discussions about PAS/EUT should not be restricted to terminally ill patients or to those suffering from physical pain per se. More generally, our results call for more attention within the debate on ELDs towards the situation of older adults who are tired of living22 due to a perceived loss of autonomy and dignity, due to loneliness or perceived burdensomeness in the context of prolonged care dependency, all of which can erode the meaning of life 23 24. In this respect, it is important to note that our study referred to attitudes among the general older population—rather than to preferences or the inclination to use PAS/EUT among actual care-dependent older adults—and, therefore, likely partially reflects negative stereotypes and fears about living as a care-dependent older adult.…”
Section: Discussionmentioning
confidence: 76%
“…Van Orden et al (2012) recently demonstrated that depression severity and self-perceived burden upon others had a significant negative impact on MIL over a 2-month period of follow-up among mental healthcare-seeking older adults with mood and anxiety disorders. Their findings support the literature demonstrating negative associations between aspects of psychopathology and MIL, and support the validity of the GSIS MIL subscale.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants specifically endorsed reduction in the presence or severity of thoughts of suicide and the wish to die, factors conceptually [58] and empirically associated with risk for death by suicide [59]. Participants additionally endorsed a significant reduction in a sense of having lost one's personal and social worth, reflecting enhanced mental health and well-being in the context of age-related life transitions and decreased burden, a variable significantly associated with suicide risk in later life [23,42]. Significant improvement in perceptions of meaning in life, an existential variable negatively associated with depression, hopelessness, suicide ideation, and the wish to hasten death [21,60,61], and positively associated with psychological well-being and longevity [22,62-64], further attests to the potential benefit of adapted IPT for at-risk older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Using core IPT techniques of interpersonal incident analysis and communication analysis, participants were helped to clarify factors contributing to their psychological pain and to improve the expression of their interpersonal needs and help alleviate despair. Feelings of emptiness, worthlessness, hopelessness, and meaninglessness are common among suicidal older adults [21,23,40]. Opportunities were thus identified for enhancing social connections, engaging in meaningful activities, and reducing exposure to painful, invalidating, or self-defeating interpersonal interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation